SURXONDARYO MINTAQASIDAGI TURIZM MATNLARINI TARJIMA QILISHDA MADANIY MOSLASHUV MUAMMOLARINING AMALIY TAHLILI - Toshtemirova Aziza Farkhadovna; Feruza Khayitova Abdikhalikovna (TADQIQOTLAR, 2026)
Relevance of the Topic The relevance of this study stems from the increasing globalization of tourism and the subsequent need for effective communication across cultures. The Surxondaryo region, rich in historical and cultural heritage, attracts diverse international tourists. However, the translation of tourism texts often encounters significant cultural adaptation problems, leading to misunderstandings and misinterpretations. This issue is critical as it directly affects the region’s tourism industry and cultural exchange. Failing to convey the intended message can deter potential visitors and diminish the region’s appeal. Therefore, understanding the cultural nuances and the specific challenges involved in translating tourism materials is essential for enhancing the effectiveness of communication in this sector and promoting the Surxondaryo region as a competitive tourist destination.